An uncommon case of metastatic undifferentiated pleomorphic soft tissue sarcoma during pregnancy: Literature review and case report - Valentina Sala; Giuliana Di Simone; Chiara Lubrano; Aida Quarenghi; Roberta Simona Rossi; Manuela Nebuloni; Irene Cetin (European Journal of Obstetrics & Gynecology and Reproductive Biology: X, 2024)
Soft tissue sarcomas accounts for 1–2% of adult malignancies. Undifferentiated pleomorphic sarcoma (UPS) is a rare subtype that lack immunohistochemical markers for a specific definition. About 18% of sarcomas are at a locally advanced stage, often requiring several cycles of chemotherapy and radiotherapy, in addition to surgery. For a young woman, this can mean delaying pregnancies with a high risk of therapy-induced ovarian damage. For this reason, proper counseling on fertility preservation plays a key role. In addition, all women of childbearing age with cancer, should be informed about the importance of planning a pregnancy to improve maternal and neonatal outcomes. We report a rare case of a 40-year-old woman with a UPS who, during CT scan after chemotherapy to decide on surgery, find out she was pregnant. After counseling, the patient decides to go ahead with the pregnancy.